What Is the evidence for endovascular thrombectomy in posterior circulation stroke? - Räty, Silja; Nguyen, Thanh N.; Nagel, Simon; Puetz, Volker; Alemseged, Fana; Abdalkader, Mohamad; Schonewille, Wouter J.; Strbian, Daniel (Seminars in neurology, 2023)
Posterior circulation infarcts comprise approximately 25% of ischemic strokes but are less often treated with recanalization therapy and have longer treatment delays compared with anterior circulation strokes. Among posterior circulation strokes, basilar artery occlusion is associated with the most severe deficits and the worst prognosis. Endovascular thrombectomy is a standard of care for patients with anterior circulation large vessel occlusion, but not until recently were the first randomized controlled trials on endovascular thrombectomy in basilar artery occlusion published. Two of the trials were neutral, whereas two others showed better functional outcome after thrombectomy up to 24 hours of symptom onset compared with best medical treatment, which in most cases had low rates of intravenous thrombolysis. According to observational data, thrombectomy seems to be safe also in isolated posterior cerebral artery occlusions and might be an option for selected patients, even if its outcome benefit is yet to be demonstrated.
Gesehen am 12.06.2024